Tanshinone IIA Improves Painful Diabetic Neuropathy by Suppressing the Expression and Activity of Voltage-Gated Sodium Channel in Rat Dorsal Root Ganglia - Ri-Ge-le, Ao; Guo, Zhuang-Li; Wang, Qi; Zhang, Bao-Jian; Kong, Da-Wei; Yang, Wen-Qiang; Yu, Yan-Bing; Zhang, Li (Experimental and Clinical Endocrinology & Diabetes, 2018)
Painful diabetic neuropathy (PDN) is one of the intractable complications of diabetes mellitus, which manifest as exaggerated pain perception. Previous studies showed that Tanshinone IIA (TIIA), one of the major bioactive extracts of Salvia miltiorrhiza Bunge, have obvious analgesic effect on different types of pain process, and the underlying analgesic mechanisms are not fully understood. The present study combined the behavioral, electrophysiological and biochemical methods to elucidate the analgesic mechanism of TIIA, using streptozotocin (STZ)-induced PDN rat models. Intraperitoneal injection (i.p.) of TIIA for 3 weeks in PDN rats significantly improved mechanical allodynia and thermal hyperalgesia. Patch clamp recordings showed that the excitability of dorsal root ganglion (DRG) nociceptive neuron was increased in diabetic state, and TIIA treatment effectively recovered the subnormality, which was achieved by preventing augments of both Tetrodotoxin-sensitive (TTX-resistant) and Tetrodotoxin-sensitive (TTX-S) sodium currents. Further, the protein expressions of voltage-gated sodium channels (VGSCs) α-subunits Nav1.3, Nav1.7 and Nav1.9 increased in DRG of diabetic rats and were normalized by TIIA application. In conclusion, this study provides evidence that the TIIA attenuated PDN by effecting VGSCs activities and expressions, indicating that the TIIA could be a promising agent for PDN treatment.
Keywords: Tanshinone IIA; Painful diabetic neuropathy; Pain perception; voltage-gated sodium channels; neuronal excitability